THE Pengembangan Modul Matematika untuk Menerapkan Model PQ4R - Novicha Muthia; Netriwati Netriwati; Iip Sugiharta (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
this study has the aim to develop learning media in the form of a module assisted by the PQ4R model in mathematics learning. The procedure used in the development of learning media is ADDIE procedure, namely analyze, design, development, implementation and evaluation. Data collection techniques used were interviews, questionnaires, documentation and tests. Data analysis techniques used are feasibility test, attractiveness test and t test. The main result of this research and development is the mathematics learning module for the PQ4R model that has been declared feasible and valid by 3 material experts with an average score of 3.42 and media experts 3.77 with each valid criterion or feasible to be used as learning media . While the attractiveness test was obtained from a small scale with an average score of 3.49 and a large scale obtained an average score of 3.71 with each of the criteria interesting. Judging from the effectiveness of media use, the results of of 2.224 and of 2.051, this means that then is accepted. Based on this, it can be concluded that the learning module for the PQ4R model influences or is effective in improving students' mathematics learning outcomes. Based on this, it can be concluded that the media that is developed is feasible and very interesting is used as a learning medium. Besides that the media that has been developed is also effective in increasing the motivation and learning outcomes of students in learning mathematics on the subject of the set.